2022
DOI: 10.14309/crj.0000000000000801
|View full text |Cite
|
Sign up to set email alerts
|

Successful Fecal Microbiota Transplant Delivered by Foley Catheter Through a Loop Ileostomy in a Patient With Severe Complicated Clostridioides difficile Infection

Abstract: Clostridioides difficile infection (CDI) is a potentially life-threatening cause of diarrhea that can result in multiple complications. Fulminant CDI that is nonresponsive to antibiotics may require surgical ileostomy or fecal microbiota transplant (FMT). We present a case of a patient with fulminant CDI requiring surgical loop ileostomy who underwent a successful FMT delivered by Foley catheter through the ileostomy with symptom resolution. Delivery of FMT using a foley catheter in a patient with an ileostomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…The patient underwent rescue FMT, which was safely delivered by a Foley catheter through the ileostomy. The case highlighted the positive contribution of the Foley catheter in multiple FMTs, avoiding re-operation and unnecessary colonoscopy [30]. The role of the Foley catheter in this case was similar to colonic TET; however, it is not as stable as colonic TET because it is not fixed to the intestinal wall.…”
Section: Colonic Tet For Microbial Therapymentioning
confidence: 74%
“…The patient underwent rescue FMT, which was safely delivered by a Foley catheter through the ileostomy. The case highlighted the positive contribution of the Foley catheter in multiple FMTs, avoiding re-operation and unnecessary colonoscopy [30]. The role of the Foley catheter in this case was similar to colonic TET; however, it is not as stable as colonic TET because it is not fixed to the intestinal wall.…”
Section: Colonic Tet For Microbial Therapymentioning
confidence: 74%
“…However, in chronic wounds this equilibrium is disrupted because of the underlying systemic disease of the patient, making it difficult to treat with commensal probiotics alone. Studies have shown the importance of maintaining healthy homoeostasis at sites of infection via microbiome transplantation, with the primary focus being on faecal transplantation for the treatment of Clostridium difficile infections and for surgical operations such as colostomy and ileostomy 116–120 . However, microbiota transplantation remains an underdeveloped area of research for the treatment of chronic wounds.…”
Section: Current Treatments Against Chronic Infectionsmentioning
confidence: 99%
“…Studies have shown the importance of maintaining healthy homoeostasis at sites of infection via microbiome transplantation, with the primary focus being on faecal transplantation for the treatment of Clostridium difficile infections and for surgical operations such as colostomy and ileostomy. 116 , 117 , 118 , 119 , 120 However, microbiota transplantation remains an underdeveloped area of research for the treatment of chronic wounds. It is generally accepted that a diverse microbiome is considered the "right recipe".…”
Section: Current Treatments Against Chronic Infectionsmentioning
confidence: 99%